Sistem Prediksi Kelulusan Ujian Sertifikasi IT Dengan Metode Waterfall - Firmansyah, Maulana; Halim, Nuciko Abdul; Imelda, Imelda (Program Studi Teknik Informatika Universitas Paramadina, 2025)
This study aims to develop a prediction system for IT certification exam success to boost candidates' confidence and identify participants who require additional training at PT Brainmatics. The main issue is how to effectively utilize historical data to produce accurate predictions and support less confident participants in better preparing for the exam. The study employs the Waterfall method due to its systematic and structured approach. The prediction system utilizes variables such as educational background, work experience, and previous test results. The development stages include needs analysis, system design, implementation, testing, and maintenance. The results show that the system provides accurate predictions with a high degree of reliability. This system assists PT Brainmatics training institutions in identifying participants who need additional support and improving the quality of IT training and certification exams